Para além da Universidade: experiências e intelectualidades indígenas no Brasil - Luiz Henrique Eloy Amado (IdeAs)
This paper aims to bring initial ideas about the analysis of the writings of indigenous intellectuals in Brazil, presenting a preliminary survey. In addition to offering a preliminary overview of indigenous production in Brazil and which in this work we are placing under an umbrella called “indigenous intellectuality”, but having clear that indigenous intelligence is not restricted to the way of doing science in Brazil, but rather on the contrary, this knowledge is born and radiates from the beaten ground of the village. We are especially interested in the impacts of the production and experiences of these indigenous intellectuals on the Brazilian indigenous movement, that is, how such individual trajectories instrumentalized in the academy's own symbols are articulating with their own indigenous knowledge and contributing effectively to the political, economic, legal and social results that take into account the worldview of indigenous communities.